Non-coding RNAs in bladder cancer, a bridge between gut microbiota and host? - Zou, Jun; Xu, Baisheng; Luo, Peiyue; Chen, Tao (Frontiers in Immunology, 2024)
In recent years, the role of gut microbiota (GM) in bladder cancer has attracted significant attention. Research indicates that GM not only contributes to bladder carcinogenesis but also influences the efficacy of adjuvant therapies for bladder cancer. Despite this, interventions targeting GM have not been widely employed in the prevention and treatment of bladder cancer, mainly due to the incomplete understanding of the complex interactions between the host and gut flora. Simultaneously, aberrantly expressed non-coding RNAs (ncRNAs) have been frequently associated with bladder cancer, playing crucial roles in processes such as cell proliferation, invasion, and drug resistance. It is widely known that the regulation of GM-mediated host pathophysiological processes is partly regulated through epigenetic pathways. At the same time, ncRNAs are increasingly regarded as GM signaling molecules involved in GM-mediated epigenetic regulation. Accordingly, this review analyzes the ncRNAs that are closely related to the GM in the context of bladder cancer occurrence and treatment, and summarizes the role of their interaction with the GM in bladder cancer-related phenotypes. The aim is to delineate a regulatory network between GM and ncRNAs and provide a new perspective for the study and prevention of bladder cancer.